Profile of Unilateral Cataract in Pediatric Patients: A 3 Year Retrospective Study: Oral Presentation - Observational Study - Resident - Lisana Himmatul Ulya; Liana Ekowati (Majalah Oftalmologi Indonesia, 2023)
Abstract Introduction & Objectives : Unilateral cataract presents from 19.6% to 55.5% of pediatric cataract in children by many previous reported studies. This condition is treatable, but delayed treatment may cause visual impairment. This study aims to understand characteristic and treatment of unilateral cataract in children. Methods : The study involved a retrospective review of medical records of patients aged 0-17 years with unilateral cataract who presented to Dr. Kariadi Hospital Semarang from 2019 to 2022. Cases of cataract secondary to causes such as trauma or uveitis were excluded. Results : Thirty-five patient was included in this study, 51% of whom were male and 49% female. The mean age at presentation is 60.49  48.23 months and mean age of onset is 36.77  45.94 months. The most common presenting complaint was whitish eye (81%) while others presented with blurred vision. All the patients had leukocoria, 28% have microcornea, 3% have persistent pupillary membrane. Half of patient (51%) have strabismus, with exotropia being the most common type (34.17%). Eight patients had congenital rubella syndrome, one patient had cytomegalovirus infection while others did not have any systemic condition related to cataract. Majority of patient (17%) treated with phacoaspiration, primary posterior capsulotomy, anterior vitrectomy and intraocular lens implantation. Intraocular lens was implanted in 71% patient and 54% patients given spectacles. Conclusion : Unilateral cataract is disease with isolated and sporadic incident. The majority of patients did not have systemic condition related to unilateral cataract. The most common treatment is phacoaspiration, primary posterior capsulotomy, anterior vitrectomy and intraocular lens implantation.